Spanish identity in the age of nations - Alvarez Junco, Jose, 1942- (Book collections on Project MUSE., 2011)
First published in Spanish in 2001, this book was quickly recognised as a monumental achievement by one of Spain's most original and engaging historians. Álvarez Junco's book is a path breaking study of the development of Spanish national identity ('the idea of Spain') from the Middle Ages to the present.